Effects of supplementing low-protein diets with sodium dichloroacetate and glucose on growth performance, carcass traits, and meat quality of growing-finishing pigs. (4th December 2021) - Xu, Yetong; Chen, Huiyuan; Wan, Ke; Zhou, Kaifeng; Wang, Yongsheng; Li, Jigang; Tang, Zhiru; Sun, Weizhong; Wu, Liuting; An, Rui; Ren, Zhongxiang; Ding, Qi; et al.
Abstract: The objective of this study was to evaluate the effects of supplementing low-protein diets with sodium dichloroacetate (DCA) and glucose on growth performance, carcass traits, and meat quality of growing-finishing pigs. A total of 80 crossbred ( Duroc × Landrace × Large White ) growing barrows (27 ± 0.4 kg body weight) were allocated randomly to one of the five treatments during three successive 4-wk periods. There were five diets in each phase. Diet 1 was the control diet with normal protein levels (CON) where protein levels in the three phases were 18%, 16.5%, and 15.5%, respectively. The dietary protein levels of Diets 2, 3, 4, and 5 (the low-protein diets, LP) were decreased by 4.5% compared to Diet 1. Additionally, Diets 3 and 4 were supplemented with an extra 120 mg/kg DCA (LP + DCA) or 1.8% glucose (LP + GLUC), respectively. Diet 5 was further supplemented with an extra 120 mg/kg DCA and 1.8% glucose (LP + DCA + GLUC). The LP + DCA diet increased the average daily weight gain of pigs compared to the CON and LP diet in phase 3 and the overall experimental period ( P < 0.001). The LP diet reduced the gain:feed ratios of the pigs compared to the CON, LP + DCA, and LP + DCA + GLUC diets in phase 1 and the overall experimental period ( P < 0.001). Furthermore, gain:feed ratios in LP + DCA and LP + DCA + GLUC groups did not differ from that of the CON group ( P > 0.10). Pigs fed the LP + DCA diet had higher pH values of meat at 24 h post-mortem than the CON group ( P < 0.05). The LP + DCA + GLUC diet increased the total protein content in the longissimus dorsi (LD) muscle of pigs, compared to the other dietary treatments ( P < 0.05), and increased the Arg and Leu contents in the LD muscle compared to the LP + DCA diet ( P < 0.05). Moreover, the LP + DCA diet induced a higher C18:1n9t percentage in the LD muscle of pigs compared to other groups ( P < 0.05). In conclusion, an LP diet reduced the feed efficiency in pigs and barely affected meat quality, whereas 120 mg/kg DCA supplementation in an LP diet improved the growth performance of growing-finishing pigs, showed modest effects on carcass traits, and improved the muscle protein content with the addition of glucose.